Integrated care competencies and their association with cross‐cultural competence among registered nurses: A cross‐sectional questionnaire survey - Maliheh Nekouei Marvi Langari; Jaana Lindström; Tarja Heponiemi; Anu‐Marja Kaihlanen; Laura Hietapakka; Hamid Heidarian Miri; Hannele Turunen (Nursing Open, 2024)
Abstract Aim To examine the association between the integrated care competencies and cross‐cultural competence of registered nurses prior to the integration of social and healthcare services in Finland. Design A descriptive correlational cross‐sectional questionnaire survey was conducted. Methods A simple random sample of 10,000 registered nurses was drawn from the Finnish Central Register of Valvira (National Supervisory Authority for Welfare and Health); 7000 of them were sent the online questionnaire, and a total of 1232 registered nurses participated in the study. We collected data using background questions, revised versions of the Competent Workforce for the Future tool in the four domains of client orientation, responsibility for personal or relative's welfare, fluency and clarity of services and access to the services and of the Cross‐Cultural Competence of Healthcare Professional tool in the four domains of motivation/curiosity, attitude, skill and emotion/empathy. Results Participants demonstrated a high level of integrated care competencies (mean = 4.00, SD ± 0.49). An association was observed between integrated care competencies and their domains of skills, motivation/curiosity, emotions/empathy, and cross‐cultural competence (p < 0.001). Female sex, older age, more working experience, employment in the private sector, and higher self‐rated competence for working in a multicultural environment were positively associated with higher integrated care competencies. Conclusion It is recommended that nurse managers and nurse educators emphasize the development of registered nurses' cross‐cultural competence alongside integrated care competencies to meet the needs of different individuals and communities when providing integrated care. Patient or Public Contribution Finnish registered nurses including all types of nurses, midwives and paramedics working the public and private healthcare, were involved in this study by responding to the online survey.